On the Optical and Radiative Properties of Atmospheric Aerosols at a Subarctic Site in Finnish Lapland - Aaltonen, Veijo (Finnish Meteorological Institute, 2023)
Atmospheric aerosols are of great importance since they affect the sun radiation directly by scattering it back to space and by absorbing the radiation energy. Indirectly, they contribute to cloud formation by acting as cloud con densation nuclei. Aerosols also cause harmful health effects such as lung cancer and cardiovascular diseases. There is a demand of measurement data of aerosols from areas in the absence of regional pollution sources. In this study, the optical and radiative properties of aerosols have been investigated based on the optical and microphysi cal data obtained over three-year period at Finnish subarctic site Pallas. The scattering coefficient at 550 nm, with total average of 7.1 ± 8.6 Mm-1, had a clear seasonal cycle with an autumn minimum and a 4 − 5 times higher summer maximum. Most of the scattering was caused by submicron aerosols, which was pronounced during late summer and autumn. The Ångström exponent also had a clear seasonal pattern, with its maximum values in late summer and minimum values during wintertime. The highest hemispheric backscattering fraction values were ob served in autumn, suggesting the domination by ultrafine particles. A cluster analysis applied to the aerosol data concluded the most polluted trajectory patterns representing air masses mostly from the Kola Peninsula, Scandina via and Russia, while the cleanest air was originating from the Arctic Ocean. Natural boreal forest contributes to aerosol formation by emitting gases which acts as precursor for biogenic secondary organic aerosols. Originated from clean marine type region, the aerosol gathers forestal characteristics when passing over the natural boreal forest in summer. The contribution of natural boreal forest aerosols to the direct radiative effect (DRE) was -(0.37− 0.74) Wm-2. Global estimate of DRE due to boreal forest is smaller than DRE owing to sea salt or dust aerosols. Ilmakehän aerosolit sirottavat auringosta tulevaa säteilyä takaisin avaruuteen ja absorboivat säteilyenergiaa. Ne vaikuttavat ...